Comparación entre el Método Directo y la Fórmula de Friedewald para Determinar los Niveles de Colesterol LDL en Caninos - Osorio, José Henry (2014)
The aim of this study was to compare the Direct method and the Friedewald formula method for the determination of LDL cholesterol in dogs. Blood samples were collected in 185 fasted dogs without sex restriction. Serum was extracted and levels of LDL cholesterol were determined by the two methods. The mean, standard deviation, and minimum and maximum values by the Direct method were 49.2 ± 16.7, 14.6 and 96.0 mg/dl, respectively, and by the Friedewald method were 65.2 ± 31.5, 4.6 and 184.2 mg/dl, respectively, with significant difference between the methods (p<0.05). The Direct method is recommended for determining LDL cholesterol levels in dogs.